2016
DOI: 10.1039/c6ra00164e
|View full text |Cite
|
Sign up to set email alerts
|

Poly(piperazinyl phosphamide): a novel highly-efficient charring agent for an EVA/APP intumescent flame retardant system

Abstract: Poly(piperazinyl phosphamide) is a kind of novel charring agent, showing highly-efficient charring capacity and good interaction with another flame-retardant component APP in flame retarding EVA.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
37
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(39 citation statements)
references
References 45 publications
2
37
0
Order By: Relevance
“…In previous researches, many articles only mentioned to intumescent systems including 2 or 3 components . In this study, we experimented up to 4 components, and the flammability was evaluated by UL‐94 vertical test.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous researches, many articles only mentioned to intumescent systems including 2 or 3 components . In this study, we experimented up to 4 components, and the flammability was evaluated by UL‐94 vertical test.…”
Section: Resultsmentioning
confidence: 99%
“…The efficiency of phosphorus‐based flame retardant (FR) depends upon not only the amount of the phosphorus element existing in the compound but also the ability to form the charred residue. Many researchers studied the flame retardancy of organophosphorus compounds derived from 4‐(hydroxy‐methyl)‐1‐oxido‐2,6,7‐trioxa‐1‐phosphabicyclo[2.2.2]octane for poly(butylene terephthalate), PP, and polyethylene and reported that these derivatives generate high‐residual char, and thus, the greater flame retardancy is achieved …”
Section: Introductionmentioning
confidence: 99%
“…4,5 During its long lifetime or applications in extreme surroundings, such as construction, shipbuilding, or in nuclear, automotive, or photovoltaic applications, 6 several service conditions (mainly the weathering exposures) are inevitable, including UV irradiation, temperature, and humidity, and sometimes even salt spray. Aluminum hydroxide (ATH) [11][12][13][14][15][16] and phosphoruscontaining flame retardants, such as aluminum diethyl phosphinate (AlPi-Et), [17][18][19][20] aluminum hypophosphite, 21 aluminum phosphate, 22 and ammonium polyphosphate (APP) [23][24][25][26] have been proposed and utilized extensively, exhibiting good flame retardancy in EVAs. 6 Accordingly, it is important and necessary to investigate the long-term durability of cables exposed under different weathering conditions, as well as the deterioration of flame retardancy.…”
Section: Introductionmentioning
confidence: 99%
“…Intumescent flame retardants, one kind of halogen‐free flame retardants have been extensively used for enhancing the flame retardancy of polymers due to high efficiency and low toxicity . In general, the intumescent flame retardants contain the ternary components, called acid source, carbonization source and gas source.…”
Section: Introductionmentioning
confidence: 99%